Analysis of the Altman, Springate, Zmijewski, and Grover Methods in Predicting Bankruptcy in Retail Electronics Sub Sector Companies Listed on the Indonesia Stock Exchange for the 2019-2022 Period - Hartono, Arif; Dita, Wahyu Riskina; Ulfah, Ika Farida (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2025)
Companies with good financial conditions are able to maintain the stability of their operational activities so that profits can increase so that the company avoids the possibility of bankruptcy. The purpose of this study is to predict the potential for bankruptcy using the Altman, Springate, Zmijewski, and Grover methods and to measure the level of accuracy of each method in predicting bankruptcy in Electronic Retail Subsector Companies listed on the IDX for the 2019-2022 period. Bankruptcy is a condition that is not expected to occur in a company where the company is unable to carry out operational activities and its financial management stops. To analyze bankruptcy predictions, researchers use the Altman, Springate, Zmijewski, and Grover methods as measuring tools for predicting potential bankruptcy. This study uses a quantitative analysis method with a descriptive research type. The sample used in this study was 6 Electronic Retail Subsector companies listed on the IDX for the 2019-2022 period with a sampling method using saturated samples. Namely, all members of the population are sampled. The data collection method in this study uses financial report documentation. The results of the study show that the company that is predicted to have the most potential to go bankrupt is PT. Globe Kita Terang tbk using all four prediction methods. The bankruptcy prediction method used in this study with the highest level of accuracy is the Zmijewski and Grover method of 66.67%.